Hexagonal boron nitride: a promising substrate for graphene with high heat dissipation. (11th May 2017) - Zhang, Zhongwei; Hu, Shiqian; Chen, Jie; Li, Baowen
Abstract: Supported graphene on a standard SiO2 substrate exhibits unsatisfactory heat dissipation performance that is far inferior to the intrinsic ultrahigh thermal conductivity of a suspended sample. A suitable substrate for enhancing thermal transport in supported graphene is highly desirable for the development of graphene devices for thermal management. By using molecular dynamics simulations, here we demonstrate that bulk hexagonal boron nitride ( h -BN) is a more appealing substrate to achieve high performance heat dissipation in supported graphene. Notable length dependence and high thermal conductivity are observed in h -BN-supported single-layer graphene (SLG), suggesting that the thermal transport characteristics are close to that of suspended SLG. At room temperature, the thermal conductivity of h -BN-supported SLG is as high as 1347.3 ± 20.5 Wm −1 K −1, which is about 77% of that for the suspended case, and is more than twice that of the SiO2 -supported SLG. Furthermore, we find that the smooth and atomically flat h -BN substrate gives rise to a regular and weak stress distribution in graphene, resulting in a less affected phonon relaxation time and dominant phonon mean free path. We also find that stacking and rotation significantly impacts the thermal transport in h -BN-supported graphene. Our study provides valuable insights towards the design of graphene devices on realistic substrate for high performance heat dissipation applications.